Therapy for Stage IV Non–Small-Cell Lung Cancer With Driver Alterations: ASCO Living Guideline. Issue 28 (1st October 2022) - Singh, Navneet; Temin, Sarah; Baker, Sherman; Blanchard, Elizabeth; Brahmer, Julie R.; Celano, Paul; Duma, Narjust; Ellis, Peter M.; Elkins, Ivy B.; Haddad, Rami Y.; Hesketh, Paul J.; Jain, Dharamvir; et al.
Abstract : Living guidelines are routinely updated guidelines that are developed for selected topic areas with rapidly evolving evidence that drives frequent change in clinical practice. These guidelines are updated on a regular schedule, based on the work of a standing panel that reviews the literature on a continuous basis. Updates will be made regularly and can be found at https://ascopubs.org/nsclc-da-living-guideline . PURPOSE: To provide evidence-based recommendations updating the 2021 ASCO and Ontario Health (Cancer Care Ontario) guideline on systemic therapy for patients with stage IV non–small-cell lung cancer (NSCLC) with driver alterations. METHODS: ASCO updated recommendations on the basis of an ongoing systematic review of randomized control trials from 2020 to 2021. RESULTS: This guideline update reflects changes in evidence since the previous update. Two studies provide the evidence base. Outcomes of interest include efficacy and safety. RECOMMENDATIONS: For patients with an anaplastic lymphoma kinase rearrangement, a performance status (PS) of 0-2, and previously untreated NSCLC, clinicians should offer alectinib or brigatinib or lorlatinib. For patients with an anaplastic lymphoma kinase rearrangement, a PS of 0-2, and previously untreated NSCLC, if alectinib, brigatinib, or lorlatinib are not available, clinicians should offer ceritinib or crizotinib. For patients with a RET rearrangement, a PS of 0-2, and previously untreated NSCLC, clinicians may offer selpercatinib or pralsetinib. In second line, for patients with a RET rearrangement who have not received RET-targeted therapy, clinicians may offer selpercatinib or pralsetinib. Additional information is available at www.asco.org/thoracic-cancer-guidelines .